Effect of Natural Deep Eutectic Solvents on Phenolic Extraction Efficiency and Antioxidant Activity of Date Seeds Extract - Heba A. Sindi; Alanood A. Alfaleh; Marya J. Hamdan (International Journal of Food and Nutritional Health, 2026)
A single Natural deep eutectic solvent (NADES) have emerged as eco-friendly alternatives to traditional toxic organic solvents, which offer enhanced extractability and bioavailability of bioactive compounds found in wasted date seeds. The aim of the study was to investigate the effect of NADES efficiency on the antioxidant activity of extracted date seeds; The physiochemical properties of three prepared NADES based on L-proline as a hydrogen bond acceptor (HBA) and different hydrogen bond donors (HBD) of glycerol, lactic acid, and citric acid were measured, then used to extract (1 g) of date seeds powder using ultrasound method, compared with conventional solvents (water and 70% ethanol). The total phenolic content (TPC) and antioxidant activity, using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, of date seeds extracts were evaluated spectrophotometrically; The highest yield of TPC for date seeds extract was found in lactic and citric acids-based NADES (38.31 ± 0.06 and 30.44 ± 0.85 mg GAE/g dw, respectively), with also the highest antioxidant activity (90.96 ± 0.48 and 90.61 ± 0.16%, respectively) compared with other solvents; The results revealed that carboxylic acid-containing NADES enhanced effectiveness, which hold promise for polyphenols extraction from date seeds with distinct antioxidant activities. Further research is warranted to explore the potential bioactivities of NADES-based extraction processes.